The neglected role of insulin‐like growth factors in the maternal circulation regulating fetal growth - Sferruzzi‐Perri, A. N.; Owens, J. A.; Pringle, K. G.; Roberts, C. T. (The Journal of physiology, 2011)
Maternal insulin‐like growth factors (IGFs) play a pivotal role in modulating fetal growth via their actions on both the mother and the placenta. Circulating IGFs influence maternal tissue growth and metabolism, thereby regulating nutrient availability for the growth of the conceptus. Maternal IGFs also regulate placental morphogenesis, substrate transport and hormone secretion, all of which influence fetal growth either via indirect effects on maternal substrate availability, or through direct effects on the placenta and its capacity to supply nutrients to the fetus. The extent to which IGFs influence the mother and/or placenta are dependent on the species and maternal factors, including age and nutrition. As altered fetal growth is associated with increased perinatal morbidity and mortality and a greater risk of developing degenerative diseases in adult life, understanding the role of maternal IGFs during pregnancy is essential in order to identify mechanisms underlying altered fetal growth and offspring programming.